Graphene Based Membranes for High Salinity, Produced Water Treatment by Pervaporation Separation - Almarzooqi, Khalfan (University of Waterloo, 2023)
Petroleum industries generate huge volumes of wastewater that is associated with oil and gas during extraction, known as produced water. It accounts for 98% of the amount extracted, and comprises diverse pollutants of salts, suspended solids, dissolved organic solutes, and dispersed oils; that require to be safely treated before being disposed to the environment, or reused for various beneficial applications. Nowadays, graphene-based membranes have shown potential as a membrane material due to their high performance and stability features. This research demonstrated the use of graphene oxide membranes supported on polyethersulfone films (GO/PES) for high salinity water, simulated produced water model (PWM), and PWM with simulated foulants treatment via the pervaporation separation technology. The membranes showed the highest water flux of 47.8 L m-2 h-1 for NaCl solutions in pervaporation testing operated at 60 oC, and salt and organic rejections of 99.9% and 56%, respectively. In addition, the membranes were tested for long-term pervaporation for 72 hours and showed a decline of 50–60% from the initial flux in the worst-case-scenario. Moreover, in-depth investigation of the Zn2+ crosslinker showed a hydrolysis reaction to Zn(OH)2, with the progress of the long-term pervaporation, in which much of it is being leached out. Consequently, since GO membranes are not stable in water, it remains challenging to be utilized in the industry. A more stable GO membrane in aqueous phase was proposed. The membrane’s stability was enhanced by divalent and trivalent metal cations of Zn2+ and Fe3+ crosslinkers, respectively, and partial reduction under vacuum. Two orders of fabrications were investigated of either crosslinking rGO (method I) or reducing M+–rGO (method II). The prepared membranes were examined for their characterization and performance. Fe3+–rGO prepared by method II showed the best organic solute rejection of 69%. Moreover, long-term pervaporation experiment was performed for 12 hours for Zn2+–rGO membranes, and revealed a drop in flux of 6% only, while Zn2+–GO membrane had a drop in flux of 24%. Additionally, the stability of the membranes was tested via an abrasion method using a rotary wheel abrader. The conducted experiments revealed that Fe3+–rGO membranes had the maximum mechanical integrity with an abrasion resistance of 95% compared to the initial control (non-reduced and non-crosslinked) GO/PES membrane.
Keywords: 2D materials; membranes; produced water; oil/water separation; pervaporation; graphene oxide; reduced graphene oxide; desalination; divalent and trivalent metal cation crosslinking